Technologically important quality indicators of low-lactose ice cream with milk and whey protein concentrates - A. A. Tvorogova; I. A. Gurskiy; Yu. I. Bogdanova (Пищевые системы, 2024)
Protein concentrates have a high biological value and contain significantly less lactose in comparison with dry skimmed milk. The use of protein concentrates in ice cream without the content of non-fat milk solids allows not only making up for protein but also developing the component composition of a product with the low content of lactose. In this regard, the study of technologically significant quality indicators of ice cream with the low content of lactose without non-fat milk solids when using milk and whey protein concentrates is an urgent task. The rheological, microstructural, color and thermostatic characteristics, as well as the oxidative stability of fat of the test samples were determined in the research. It has been found that viscosity decreased by 1.8-2.6 times when using whey proteins. The use of protein concentrates led to an increase in hardness and adhesiveness by 2.2-4.1 and 1.6-5.0 times, respectively, but did not significantly affect the thermal stability. The mass fraction of fat had the greatest influence on these characteristics. The study of color characteristics of ice cream made it possible to reveal a decrease in the yellowness index when using milk protein concentrate. It has been established that color differences in most of the samples were not recognizable to the human eye. The induction period was characterized by the lowest value in the samples with whey proteins, thus indicating a probability of a faster oxidation process in them. The use of protein concentrates did not have a significant effect on ice crystals. The stability of the air phase was significantly reduced when using the whey proteins. A multivariate analysis of the studied samples divided them into the control and the samples containing protein concentrates. Based on the technologically significant quality indicators, the use of milk protein concentrates in the production of low-lactose ice cream is more preferable than the use of whey protein concentrates.